2022
DOI: 10.3390/life12060910
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk of Astrocytes and Other Cells during Ischemic Stroke

Abstract: Stroke is a leading cause of death and long-term disability worldwide. Astrocytes structurally compose tripartite synapses, blood–brain barrier, and the neurovascular unit and perform multiple functions through cell-to-cell signaling of neurons, glial cells, and vasculature. The crosstalk of astrocytes and other cells is complicated and incompletely understood. Here we review the role of astrocytes in response to ischemic stroke, both beneficial and detrimental, from a cell–cell interaction perspective. Reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 224 publications
0
33
0
3
Order By: Relevance
“…42 The A1-type astrocyte and M1-type microglia are viewed as causes of pro-inflammatory activities, synaptogenesis loss, white matter damage, and neuronal death, whereas the A2-type astrocytes and M2-type microglia are inflammatory-resolving and promote synaptic repair, growth, and neuronal survival. 8,9,42,43 The progesterone signaling pathway participates in the suppression of inflammation in neurological diseases, and progesterone treatment has been shown to inhibit astrocytosis, microgliosis, and oxidative stress after brain trauma in rodents. 39,44 Jiang et al 45 showed that intraperitoneal injection of progesterone suppressed TNFα levels in ischemic mouse brains, and we have consistently found that progesterone alleviates HIE-induced brain injury by regulating the activation of TNF signaling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…42 The A1-type astrocyte and M1-type microglia are viewed as causes of pro-inflammatory activities, synaptogenesis loss, white matter damage, and neuronal death, whereas the A2-type astrocytes and M2-type microglia are inflammatory-resolving and promote synaptic repair, growth, and neuronal survival. 8,9,42,43 The progesterone signaling pathway participates in the suppression of inflammation in neurological diseases, and progesterone treatment has been shown to inhibit astrocytosis, microgliosis, and oxidative stress after brain trauma in rodents. 39,44 Jiang et al 45 showed that intraperitoneal injection of progesterone suppressed TNFα levels in ischemic mouse brains, and we have consistently found that progesterone alleviates HIE-induced brain injury by regulating the activation of TNF signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Resting astrocytes (A0) and microglia (M0) can be switched to their activated forms, either A1/M1 (neurotoxic) or A2/M2 (neuroprotective), in response to ischemic stroke 42 . The A1‐type astrocyte and M1‐type microglia are viewed as causes of pro‐inflammatory activities, synaptogenesis loss, white matter damage, and neuronal death, whereas the A2‐type astrocytes and M2‐type microglia are inflammatory‐resolving and promote synaptic repair, growth, and neuronal survival 8,9,42,43 . The progesterone signaling pathway participates in the suppression of inflammation in neurological diseases, and progesterone treatment has been shown to inhibit astrocytosis, microgliosis, and oxidative stress after brain trauma in rodents 39,44 .…”
Section: Discussionmentioning
confidence: 99%
“…This process is thought to be critical for the repair and recovery of the brain after a stroke. Reactive astrocytes also play an important role in forming new blood vessels after stroke, which is essential for the survival and integration of new neurons in the brain [ 218 , 219 ]. Several signaling pathways have been proposed to play roles in the adult neurogenic response to ischemia-induced stroke.…”
Section: Neurogenesis In Strokementioning
confidence: 99%
“…In addition, these cytotoxic agents activate inducible pathways NO synthase (iNOS) and cyclooxygenase-2 (COX-2), which impair endothelial cells [ 29 ]. Following ischemic stroke, the expression of MMPs is responsible for disrupting the BBB, aggravating cerebral oedema, hemorrhagic transformation, and, ultimately, death of neuronal and glial cells [ 30 ].…”
Section: An Overview Of the Pathogenesis Of Cerebral Ischemiamentioning
confidence: 99%